Rice husk derived nanosilica supported Cu(ii) complex: an efficient heterogeneous catalyst for oxidation of alcohols using TBHP. Issue 115 (5th November 2015) - Gogoi, Nibedita; Begum, Tahshina; Dutta, Smarika; Bora, Utpal; Gogoi, Pradip K.
Abstract : We have developed a heterogenized catalyst of Cu(ii ) complex immobilized onto nanosilica obtained from rice husk (RH), through Schiff-base condensation between 3-aminopropyltriethoxysilane (APTES) functionalized nanosilica and acetamide. Abstract : We have developed a heterogenized catalyst of Cu(ii ) complex immobilized onto nanosilica obtained from rice husk (RH), through coordination of imine, generated via Schiff-base condensation between 3-aminopropyltriethoxysilane (APTES) functionalized nanosilica and acetamide. The synthesized catalysts were characterized by FT-IR, XRD, BET surface area measurements, ESR, SEM-EDX and ICP-AES. The synthesized catalyst showed excellent activity towards controlled oxidation of different primary and secondary alcohols in the presence of tert -butyl hydrogen peroxide (TBHP). Furthermore, the catalysts could be recovered by simple filtrations and can be reused upto many consecutive cycles without loss in activity.